Thyristor-based flexible ac transmission system for controlling the vanadium redox flow battery - Ontiveros, Leonardo Javier (2013)
The vanadium redox flow battery (VRB) is a large stationary energy storage system; which presents high-speed response and overload capacity characteristics. The VRB produces a dc voltage between two terminals; so a power conditioning system (PCS), composed principally by a dc/ac Flexible ac Transmission System (FACTS), is required in order to connect the battery to the power system. In this regard, this paper proposes a new FACTS compensator for controlling the VRB based in a 12-pulse thyristor converter with commutated capacitors on the ac side (TCCC). This type of compensator offers a good transient response with low power converter losses. Simulations of the FACTS compensator employing Matlab/Simulink software validate the proposal and show the good performance of the proposed device.